Glucocorticoid-loaded liposomes induce a pro-resolution phenotype in human primary macrophages to support chronic wound healing. (September 2018) - Gauthier, Anne; Fisch, Andreas; Seuwen, Klaus; Baumgarten, Birgit; Ruffner, Heinz; Aebi, Alexandra; Rausch, Martin; Kiessling, Fabian; Bartneck, Matthias; Weiskirchen, Ralf; Tacke, Frank; Storm, Gert; et al.
Abstract: Glucocorticoids are well established anti-inflammatory agents, however, their use to treat chronic inflammatory diseases is limited due to a number of serious side effects. For example, long-term local treatment of chronic wounds with glucocorticoids is prohibited by dysregulation of keratinocyte and fibroblast function, leading to skin thinning. Here, we developed and tested liposome formulations for local delivery of dexamethasone to primary human macrophages, to drive an anti-inflammatory/pro-resolution phenotype appropriate for tissue repair. The liposomes were loaded with the pro-drug dexamethasone-phosphate and surface-modified with either polyethylene glycol or phosphatidylserine. The latter was used to mimic phosphatidylserine-harboring apoptotic cells, which are substrates for efferocytosis, an essential pro-resolution function. Both formulations induced a dexamethasone-like gene expression signature in macrophages, decreased IL6 and TNFα release, increased secretion of thrombospondin 1 and increased efferocytosis activity. Phosphatidylserine-modified liposomes exhibited a faster uptake, a higher potency and a more robust phenotype induction than polyethylene glycol-modified liposomes. Fibroblast and keratinocyte cell cultures as well as a 3D skin equivalent model showed that liposomes applied locally to wounds are preferentially phagocytosed by macrophages. These findings indicate that liposomes, in particular upon shell modification with phosphatidylserine, promote dexamethasone delivery to macrophages and induce a phenotype suitable to support chronic wound healing.